تصميم ازياء موحدة لطلبة المدارس الابتدائية (Journal of the College of Basic Education, 2022)
This study is based on research on the subject of designing uniforms for primary school students. The designs of costumes for students aged (6-12) years, which need the designer to take into account in his designs their suitability for the student and their conformity to his body, and to be as comfortable as possible, because the student in this age stage is in it. A lot of movement and play, so the designer has to depend in his design of children’s clothes on studying the type of material (fabric) and trying to form it in a way that suits the child’s body by translating the ideas that revolve in his mind and that are commensurate with the flexibility of the fabric and its thickness and the applied designs implemented on it, as he organizes the relationships Between the fabric and the child who wears these clothes, the designer builds his design work on the new idea and the line and its harmony with the color and the material in terms of the texture composition, the quality of the material, its properties, its treatment and its agreement with the nature of the body and taking into account the comfort required for the child to wear it. Where he describes the models for the two groups, females and males, within the province of Baghdad / Karkh and Rusafa, and in order to reach the desired goals in this study, the researcher divided the study into four chapters, the first chapter includes a review of the importance of fashion through the research problem. relates to him. As for the second chapter, it dealt with four topics related to the theoretical framework. The first topic dealt with the topic (properties of the materials used in the implementation of the uniform). The second topic dealt with the topic (the colors used in the implementation of the uniform).As for the third topic, it was devoted to (factors that affect fashion design), and the fourth topic dealt with the topics of (physiological influences of gender and age and their relationship to fashion designs) and (structural design in the design and implementation of children's fashion). With regard to the third chapter, it included the research procedures that included the research methodology, the research community and its sample, the research tool and the construction process carried out by the researcher, where the form that is the research tool was built, and it was discussed in accordance with the research objectives, achieving results related to the goal of the research, as well as the results and recommendations And the necessary proposals, which were reviewed through the fourth chapter.